QUESTION TO AMERICAN PEOPLE’S COMMITMENT ON HUMAN RIGHTS IN GEORGE TILLMAN JR’S MEN OF HONOR - Khoiron, Agus Muhammad Asyiq (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2013)
This study is attempted to analyze question or critique toward American people’s commitment in a movie entitled Men of Honor movie. The objectives are: 1) to identify what practices of human rights violation are revealed in the movie, 2) to investigate how the practices are assumed to be a question on American people’s commitment towards Human Rights. The writer uses qualitative descriptive research and structuralism approach in this research. Source of the data is the movie script and scenes of in the movie. The data collected in this research are consisting of words, phrases, sentences and implicit meaning found in scenes laid in the movie. In conducting this research, I used observation sheets as the instrument. The data are collected by reading the movie script, identifying supportive text, inventorying the data into table, and classifying the data. From the analysis the writer concluded that (1) the United States of America break the civil war act, the Executive order 8802, and the universal declaration of human rights.